Low Klotho/Fibroblast Growth Factor 23 Ratio Is an Independent Risk Factor for Renal Progression in Chronic Kidney Disease: Finding From KNOW-CKD - Kim, Hyo Jin; Kim, Yunmi; Kang, Minjung; Kim, Seonmi; Park, Sue Kyung; Sung, Suah; Hyun, Young Youl; Jung, Ji Yong; Ahn, Curie; Oh, Kook-Hwan (Frontiers in Medicine, 2022)
Background: We aimed to evaluate soluble klotho and circulating fibroblast growth factor 23 (FGF23) ratio as a risk factor for renal progression, cardiovascular (CV) events, and mortality in chronic kidney disease (CKD). Methods: We analyzed 2,099 subjects from a CKD cohort whose soluble klotho and C-terminal FGF23 levels were measured at enrollment. The klotho to FGF23 ratio was calculated as klotho values divided by FGF23 values + 1 (hereinafter called the klotho/FGF23 ratio). Participants were categorized into quartiles according to klotho/FGF23 ratio. The primary outcome was renal events, defined as the doubling of serum creatinine, 50% reduction of estimated glomerular filtration rate from the baseline values, or development of end-stage kidney disease. The secondary outcomes consisted of CV events and death. Changes in CV parameters at the time of enrollment and during follow-up according to the Klotho/FGF23 ratio were also examined. Results: During the follow-up period of 64.0 ± 28.2 months, 735 (35.1%) and 273 (13.0%) subjects developed renal events and composite outcomes of CV events and death, respectively. After adjustment, the first (HR: 1.36; 95% CI: 1.08–1.72, P = 0.010) and second (HR: 1.45; 95% CI: 1.15–1.83, P = 0.002) quartiles with regard to the klotho/FGF23 ratio showed elevated risk of renal events as compared to the fourth quartile group. There was no significant association between klotho/FGF23 ratio and the composite outcome of CV events and death. The prevalence of left ventricular hypertrophy and vascular calcification was higher in the low klotho/FGF23 ratio quartiles at baseline and at the fourth-year follow-up. Conclusions: Low klotho/FGF23 ratio was significantly associated with increased renal events in the cohort of Korean predialysis CKD patients